2001
DOI: 10.1029/2000ja000384
|View full text |Cite
|
Sign up to set email alerts
|

Ion acoustic damping effects on parametric decays of Alfvén waves: Right‐hand polarization

Abstract: Abstract. We study ion acoustic damping effects on parametric decays of right-handpolarized electromagnetic waves. We do this because ion beams have been observed in a variety of space environments, and consequently, these waves can exist in those places. Damping effects are incorporated into the model by adding to the longitudinal component of the equation of motion a collision-like term. Like for left-hand-polarized waves, the effect of damping is twofold. On the one hand, damping decreases the maximum growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…However, a fluid model is sufficient to provide a general survey of possible wave couplings, saturation effects, and nonlinear purely electrostatic instabilities. Although it would be desirable to solve the problem using kinetic theory, hybrid simulations seem to confirm the results obtained by using a collision like term in the fluid equations in order to simulate Landau damping [ Inhester , 1990; see Hollweg et al , 1993; Vasquez , 1995; Gomberoff , 2000; Gomberoff and Araneda , 2001; Gomberoff , 2000; Gomberoff et al , 2001, 2005; Araneda et al , 2007].…”
Section: Discussionmentioning
confidence: 77%
“…However, a fluid model is sufficient to provide a general survey of possible wave couplings, saturation effects, and nonlinear purely electrostatic instabilities. Although it would be desirable to solve the problem using kinetic theory, hybrid simulations seem to confirm the results obtained by using a collision like term in the fluid equations in order to simulate Landau damping [ Inhester , 1990; see Hollweg et al , 1993; Vasquez , 1995; Gomberoff , 2000; Gomberoff and Araneda , 2001; Gomberoff , 2000; Gomberoff et al , 2001, 2005; Araneda et al , 2007].…”
Section: Discussionmentioning
confidence: 77%
“…(5), are invariant under a rotation through an angle of 180 o . Therefore, it is sufficient to analyze the solutions in the upper half ω − k plane [9,10,20,14,15,16]. Note that for A = 0, only the ion-acoustic modes depend on the temperature.…”
Section: Dispersion Relationmentioning
confidence: 99%
“…The effect and the evolution of the beam for right and left handed polarized waves, have also been studied by using simulation experiments [17]. These studies have considered linearly stable systems [9,10,14,15,16]. Proton beams observed in the solar wind display large drift velocities which can be larger than the necessary velocity to generate a linear beam-plasma instability [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the compression effect is taken into account, the Alfvén waves will become unstable to the parametric instabilities (Galeev & Oraevskii 1963;Goldstein 1978;Wong & Goldstein 1986;Jayanti & Hollweg 1993a, 1993bHollweg 1994;Gomberoff et al 2001;Del Zanna et al 2001;, which has been a hot topic in the plasma community since the 1960s. Galeev & Oraevskii (1963) first studied the evolution of a monochromatic Alfvén wave and showed that it is unstable to the parametric decay in a low beta plasma.…”
Section: Introductionmentioning
confidence: 99%